Local injection of vasopressin reduces the blood loss during cesarean section in placenta previa. Issue 5 (21st April 2014) - Kato, Sosuke; Tanabe, Akiko; Kanki, Kazuyoshi; Suzuki, Yusuke; Sano, Takumi; Tanaka, Kentaro; Fujita, Daisuke; Terai, Yoshito; Kamegai, Hideki; Ohmichi, Masahide
Abstract Aim The aim of this study was to evaluate the effect of local injection of vasopressin on blood loss and secondary impact on complications during cesarean section in patients with placenta previa. Material and Methods We retrospectively reviewed the medical records of all patients diagnosed with placenta previa admitted to our hospital. Two consecutive periods were compared. During period B, 59 patients underwent the local injection of a vasopressin solution (4 U in 20 mL of saline) into the placental implantation site after placental delivery. During period A, 50 patients underwent cesarean section without vasopressin injection, and were analyzed as a control group. The estimated blood loss was recorded, as were the complications during surgery. In addition, the expression of the vasopressin V1α receptor in uterine smooth muscle was evaluated by immunohistochemistry. Results The mean estimated blood loss was significantly lower in the vasopressin group than in the control group. There were no statistically significant differences with surgical complications. The vasopressin V1α receptor was highly expressed in smooth muscle cells in the lower segment of the uterine body, whereas the immunoreactivity for the oxytocin receptor was faint in the lower segment. Conclusion The local injection of vasopressin into the placental implantation site significantly reduced the blood loss without increasing the morbidity.